Patch Antenna for Future 5G Wireless Applications with DGS - Dr. M. Ranga Rao, Dr. Mukil Alagirisamy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A compact size patch antenna resonating at frequency 3.6GHz is presented in this paper. The designed patch antenna is simple in structure and fed using microstrip line. The antenna is designed keeping in mind the specification proposed by Telecom Regulatory Authority of India (TRAI). Proposed antenna shows good results in term of return loss, directivity, VSWR and gain. FR4 is used as a substrate of the proposed patch antenna, while the antenna is simulated using Higher Frequency Structural Simulator (HFSS) software.